Incidence, predictors and management of left main coronary artery stent restenosis: a comprehensive review in the era of drug-eluting stents. - De Caterina, A; Cuculi, F; Banning, A (2013)
International guidelines recommend surgical revascularisation for unprotected left main (ULM) coronary artery disease. The introduction of drug-eluting stents (DES) as an emergency therapy has resulted in increasing numbers of patients having stents placed in ULM. As a consequence, important data on the safety and long-term outcome of PCI for ULM have progressively accumulated over recent years, derived mainly from registries rather than prospective randomised trials. These studies indicate that restenosis of the ULM still represents the main predictor of clinical events following stenting. However, the observed incidence is highly variable amongst the published studies and there is little data about the clinical management of restenosis of stents placed in the ULM. In the present paper we review the available literature regarding ULM restenosis, identify its predictors and suggest an algorithm for optimal management.